Moodle platform for teaching reading comprehension - Velasco García, Betty Magdalena; Tulcán Benavides, Fabián Laureano (SATHIRI, 2025)
The study focused on the creation of a virtual classroom on the Moodle platform, designed based on the ADDIE methodology, for teaching reading comprehension in sixth-year students of Basic General Education. The research arose from the need to innovate in pedagogical strategies and to take advantage of new information and communication technologies (ICT). Difficulties in the students' reading comprehension levels and the strategies used by teachers in their pedagogical practice were identified. The study adopted a mixed approach and a non-experimental, descriptive and cross-sectional design, using questionnaires to collect data on both the level of reading comprehension of the students and the pedagogical strategies of the teachers. The findings showed that 91.4% of the students had difficulties identifying the main ideas of the texts, and 75.7% had problems inferring the consequences of the facts read. This research aimed to innovate pedagogical strategies and maximize the use of ICT to improve learning in reading comprehension. It was concluded that the implementation of a virtual classroom in Moodle, designed with the ADDIE methodology, together with teacher training and the creation of support materials, can be an effective solution to address the observed deficiencies and strengthen reading comprehension skills in students.
Keywords: Moodle Platform; Reading Comprehension; Teaching; technological Tools; ADDIE Methodology